TOWARD A NEW THEOLOGY FOR A RELIGIOUSLY RESTLESS REGION: The Accommodation of Local Traditions into Islamic Law in Lombok (State Islamic University (UIN) of Sunan Ampel Surabaya, 2019)
The issue of local traditions and their position in Islamic law frequently still sparks disputes, tensions, and conflicts among Muslims in Lombok. Large number of Muslims willingly practice such traditions in their life, such as celebrating Islamic historical events such as maulid al-nabi (the prophet birthday), isra mi‘raj, and collective zikr while the others fiercely abhor them. For example. This article aims at delve on such issues to trace the intellectual roots of such difference, and to find further explanation in the view of Islamic legal theory. By qualitative analysis in normative, and sociological perspective, this research finds that the real thoughts of the early pious generation (salaf al-salih) are generally not as rigid as imagined, as claimed by many people. Finally, this research also finds, and constructs eight gates for accommodation of various recent cultural innovations, and local traditions, with specil reference in Lombok, into the construction of Islamic legal theory with certain conditions.